The Molecular Organization of Self-awareness: Paralimbic Dopamine-GABA Interaction - Lou, Hans C.; Rømer Thomsen, Kristine; Changeux, Jean-Pierre (Frontiers in Systems Neuroscience, 2020)
The electrophysiology of the paralimbic network (“default mode”) for self-awareness has drawn much attention in a couple of decades. In contrast, knowledge of the molecular organization of conscious experience has only lately come into focus. We here review newer data on dopaminergic control of awareness, particularly in self-awareness in humans. These results implicate mainly dopaminergic neurotransmission and the control of GABAergic function directly in the paralimbic network. The findings are important for understanding addiction, developmental disorders, and dysfunctional consciousness.